PENGARUH MODEL PEMBELAJARAN KONSIDERASI TERHADAP SIKAP TOLERANSI SISWA PADA KOMPETENSI DASAR MENGHARGAI KEBERAGAMAN SUKU, AGAMA, RAS, DAN ANTAR GOLONGAN DALAM BINGKAI BHINNEKA TUNGGAL IKA - Agustiningsih, Martha Yuliana; Gunawati, Dewi, Winarno (Prodi PPKn FKIP UNS, 2017)
ABSTRACTThe objective of research was to find out whether or not there is an effect of consideration learning model on students? tolerance in basic competency of appreciating ethnic, religion, race diversities and classes in the framework of Bhinneka Tunggal Ika in SMP Negeri 1 Polokarto in the school year of 2016/2017.This study employed an experimental method with true experimental design with Posttest Only Control Design. The sampling tecnique used was cluster random sampling. Tecnique of collecting data used were: document analysis, observation and questionnaire methods. The data prerequisite analysis usedthe normality test and homogeneity test, and the proposed hypotheses of the research werw tested by using the t-test. Considering the result of research, it could be concluded that there was an effect of consideration learning model on student?s tolerance in the 7th graders of the SMP Negeri 1 Polokarto in basic competency of appreciating ethnic, religion, race diversities and classes in the framework of Bhinneka Tunggal Ika. This is can be proved by the result oh the research shows that the value of the tcount was 8.87 at the significance level of 5% with the dk = n1 + n2 ? 2 (30 + 30-2 = 58), so that the value of the ttable was 2.001(interpolation). The value of the tcount = 8.87 was greater than that of the ttable = 2.001, and the average score of students? tolerance for experiment class = 120.833 and 104.67 for those in control class. When it was converted into 0-100 scale, the mean score of students? tolerance in experiment class was 88.84 and 76.96 for those in control class. It means that the grade taught using consideration learning model was better than control grade using conventional learning model. Keywords: consideration model, tolerance attitude